INVESTIGATION ON EFFECTS OF BLENDING RATIO AND TEMPERATURE ON SYNGAS QUALITY AND PERFORMANCE OF CO-GASIFICATION - AHMAD TAMILI, SITI NORAZILAH (2019)
Gasifier has been proven feasible for the generation of electricity. Reliance on single biomass especially for seasonal crops can lead to disruptions in gasification. Hence, co-gasification with different biomass is proposed to ensure a continuous biomass supply for power generation. By considering low-cost biomass supply and non-seasonal crops such as coconut shell (CS) as a biomass feedstock. In this study, CS is used as a primary fuel due to its good physicochemical properties. CS is co-gasified with corn residues (CR) and grass (G) to study the quality of syngas and performance of co-gasification at various biomass blending ratio (20:80, 50:50, 60:40.) and temperature 700-900ºC.